Donkeys and hedges - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2002)
The president of the Agroforestry Association of Burkina Faso, Kinda Doriva, tells of his months-long mission to Liberia where he worked to 'introduce new tree plants, and fifty donkeys, to help local communities to rebuild after seven years of war....